Association between weight-adjusted-waist index and anxiety among adults in the National Health and Nutrition Examination Survey (NHANES), 2007–2012 - Liang, Xiao; Chen, Kai; Xia, Yongcan; Ding, Siyuan; Wu, Hao; Huang, Lijuan; Chen, Zhenlin; Yan, Yuqian (Frontiers in Nutrition, 2025)
Background and aimsAnxiety is a pervasive mental health concern and has evolved into a multifaceted and pressing global health concern. Despite this, the connection between the weight-adjusted waist index (WWI) and anxiety symptoms remains unexplored. Therefore, the objective of this study was to evaluate the relationship between anxiety symptoms and WWI.MethodsParticipants were recruited from the National Health and Nutrition Examination Survey (NHANES) spanning the years 2007 to 2012. Anxiety was evaluated based on the patients’ self-reported number of anxious days per month. WWI was calculated by dividing the waist circumference (measured in centimeters) by the square root of the weight (measured in kilograms). To examine linear and non-linear associations between the WWI and anxiety, we employed survey-weighted multivariable logistic regression and generalized additive models. Subgroup analyses were also conducted.ResultsThis study comprised 14,677 participants, with 3,745 of them experiencing a state of anxiety. WWI exhibited a positive correlation with anxiety, as evidenced by a fully adjusted odds ratio of 1.11. Upon converting WWI into a categorical variable based on quartiles, participants in the highest quartile had a significantly elevated risk of anxiety compared to those in the lowest quartile. Furthermore, subgroup analyses indicated that the link between WWI and anxiety was more robust among individuals who identified as female, were under 50 years old, were non-Hispanic Black, were separated, were non-smokers, and were non-heavy drinkers.ConclusionThis study uncovered a notable positive correlation between WWI and anxiety, warranting further validation through future research endeavors.